Does a Personal or Family History of Malignancy Preclude the Use of Immunomodulators and Biologics in IBD. Issue 2 (February 2015) - Kalman, Richard S.; Hartshorn, Kevan; Farraye, Francis A.
Abstract : Abstract: The medical treatment for inflammatory bowel disease (IBD) has improved over the past 20 years. Although the routine use of immunomodulators and biologic agents in the treatment of IBD in the modern era has been a great achievement, these medicines are associated with rare but serious adverse events. In addition to the infectious complications, there are data to suggest that some of these agents are associated with higher rates of malignancy. In a patient with a history of cancer, or a family history of cancer, the gastroenterologist must be prepared to answer questions about the oncogenic potential of these agents. Thiopurines have been associated with a small increased risk of lymphoma in patients with IBD. In addition, an association with skin cancer has been established. Methotrexate is generally considered safe in patients with a history of cancer. There may be a small risk of lymphoma and possibly skin cancer with anti-tumor necrosis factor agents, but determining the cancer risk of these medications is difficult as they are often used in combination with thiopurines. In general, a family history of cancer should not influence a patient's medical regimen. Treatment for a patient with a personal history of cancer must be individualized and take into account the type and stage of cancer, time since completion of therapy, and the opinion of an oncologist. Abstract : Article first published online 12 September 2014.